Effect honje forest fruit juice administration on hemoglobin levels following mercury chloride treatment in mice - Iskandar, Aiza Sabina Putri; Ruyani, Aceng; Parlindungan, Deni; Johan, Henny; Mayub, Afrizal (STKIP Persada Khatulistiwa Sintang, 2025)
Exposure to mercury chloride (HgCl?) is known to induce oxidative stress, which negatively affects the hematological system, including a decrease in hemoglobin levels. This study aims to analyze the effect of honje fruit juice (Etlingera hemisphaerica), known for its high antioxidant content, on hemoglobin levels in mice (Mus musculus) exposed to mercury chloride. This study used an experimental method involving several groups of mice, namely group K1 (control), group K2 (given honje fruit juice), and group K3 (injected with mercury and given honje fruit juice). Hemoglobin levels were measured using a Sahli tube. The results showed that honje fruit juice significantly increased hemoglobin levels in mice exposed to mercury chloride compared to the control group. These findings indicate that the antioxidant content in honje fruit can help reduce the toxic effects of mercury chloride on the circulatory system. Therefore, honje fruit juice has the potential to be developed as a natural therapeutic agent in efforts to mitigate the toxic effects of mercury chloride.